1956
DOI: 10.3181/00379727-92-22553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypophysectomy and Growth Hormone on Ploidy Distribution and Mitotic Activity of Rat Liver.

Abstract: In a recent cytuphotometric study of the effects of growth hormone on rat liver protein and nucleic acids, Di Stefano, et al. ( 1 ) reported that, within a given class of ploidy. the deoxyribose nucleic acid ( DK44) content of liver nuclei was not affected either by hypophysectomy or by the administration of a purified grolwth hormone preparation. However, differences were noted in ratios of diploid and tetraploid nuclei in livers of hypophysectomized rats as compared with hypophysectomized rats treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1957
1957
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The work of Stefano & Diermeier (1956) on the effect of growth hormone upon the development of polyploidy in the liver is in keeping with the hypothesis that growth hormone is important in the growth of the liver. Proof of the hypothesis requires work on liver regeneration in hypophysectomized rats.…”
Section: I957supporting
confidence: 63%
“…The work of Stefano & Diermeier (1956) on the effect of growth hormone upon the development of polyploidy in the liver is in keeping with the hypothesis that growth hormone is important in the growth of the liver. Proof of the hypothesis requires work on liver regeneration in hypophysectomized rats.…”
Section: I957supporting
confidence: 63%
“…As should be noted, however, polyploidy (the replication of DNA without nuclear division) in liver cells may limit direct extrapolation of muscle-tissue relationships (Cheek et al, 1965;Cheek and Hill, 1970). Both GH (Di Stefano and Diermeier, 1956;Epstein, 1967) and thyroid hormones (Swartz and Ford, 1968) are necessary for general mitosis and polyploidy to occur in the liver. Both GH (Di Stefano and Diermeier, 1956;Epstein, 1967) and thyroid hormones (Swartz and Ford, 1968) are necessary for general mitosis and polyploidy to occur in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…
Polyploidy in the cells of the hepatic parenchyma is known to be influenced by changes in the endocrine state produced by hypophysectomy and growth hormone administration (Di Stefano and Diermeier, 1956;Leuchtenberger, Helweg-Larsen and Murmanis, 1954). We have confirmed the effects of both the former (Geschwind, Alfert and Schooley, 1958) and the latter (see below) on liver polyploidy, but have shown that although the hormonal environment may normally play a role in the development of polyploidy, it is not indispensable to that development (Geschwind, Alfert and Schooley, 1958).In the course of experiments designed to investigate the hormonal factors necessary to stimulate growth in the genetic dwarf mouse (Cole, Geschwind, and Bern, unpublished experiments), it was found that highly purified bovine growth hormone preparations were far less effective in stimulating body growth than were the crude preparations used for this purpose by Fo'nss-Bech (1947).
…”
mentioning
confidence: 99%
“…Polyploidy in the cells of the hepatic parenchyma is known to be influenced by changes in the endocrine state produced by hypophysectomy and growth hormone administration (Di Stefano and Diermeier, 1956;Leuchtenberger, Helweg-Larsen and Murmanis, 1954). We have confirmed the effects of both the former (Geschwind, Alfert and Schooley, 1958) and the latter (see below) on liver polyploidy, but have shown that although the hormonal environment may normally play a role in the development of polyploidy, it is not indispensable to that development (Geschwind, Alfert and Schooley, 1958).…”
mentioning
confidence: 99%